Legal Liability of Parties to Lease Agreements Concerning Income Tax Withholding and Remittance under Law Number 7 of 2021 on the Harmonization of Tax Regulations - Herlambang Herlambang; Appe Hutauruk; Hotman Sinambela (SEAN Institute, 2026)
Lease agreements create not only contractual rights and obligations between lessors and lessees but also taxation obligations, particularly those related to the withholding and remittance of Income Tax (PPh) on rental income. This study aims to analyze the legal responsibilities of parties to lease agreements concerning Income Tax withholding and remittance under Law Number 7 of 2021 on the Harmonization of Tax Regulations and to examine the legal consequences and forms of legal protection arising from non-compliance. This study employs a juridical-empirical legal research method using statutory and conceptual approaches. Data were obtained through literature review and interviews and were analyzed qualitatively using a descriptive-analytical method. The findings indicate that tax obligations arising from lease transactions are statutory obligations governed by mandatory public law and therefore cannot be excluded or transferred solely through contractual provisions. A party legally designated as a withholding agent remains responsible for withholding, remitting, reporting, and documenting Income Tax in accordance with applicable regulations. Failure to fulfill these obligations may result in administrative sanctions and, under certain circumstances, civil or criminal liability. Legal protection is provided through preventive and repressive mechanisms. The study concludes that synchronization between contractual arrangements and taxation regulations, supported by improved tax awareness, administrative capacity, and effective supervision, is essential to strengthen legal certainty and tax compliance in lease transactions.